Power performance analysis on secure and efficient authentication protcols in mobile devices (International Journal of Engineering and Computer Science, 2017)
Mobile phone in our present life has become an important device for communication, selective from formal and informal talks to sharing confidential and secure information. This secure information includes personal communication to large business deals. Thus, there is a need to guarantee security to those applications which use to send confidential information. Focusing to meet the mobile users’ demand, many cryptographic protocols are chosen based on confidentiality, integrity and authentication. Public Key Cryptography is a better solution that fulfills the above mentioned necessities. Applications that use public key cryptography deals with computing power, key size to measure the efficiency of the protocol. This work mainly focuses on the performance attributes of the ECC algorithm modified with its addition and multiplication points after generating a prime number, which leads to few changes in the algorithm parameters of encryption and decryption process to improve performance with limited power consumption. The proposed algorithm studied and compared with its conventional one, is highly secured for a mobile communication along with minimum power and current consumption. The protocol energy efficiencies are measured based on the consumption of current, power against time. Experiments results that the proposed protocol consumes less power and current when compared with the conventional ECC algorithm